ASUPAN IODIUM ANAK USIA SEKOLAH DI INDONESIA - Kartono, Djoko; Mulyantoro, Donny K. (PERSATUAN AHLI GIZI INDONESIA, 2010)
IODINE INTAKE AMONG SCHOOL-AGED CHILDREN IN INDONESIAIodine Deficiency Disorders (IDD) has been recognized in many areas mainly around volcanoes in Indonesia for a long time. Fortification of salt with iodine has been used for national IDD control for over two decades. Monitoring survey of iodized salt was conducted regularly by Central Bureau of Statistics and Ministry of Health. In 2007, national survey on iodine was conducted by Ministry of Health through Basic Health Research. The objective of this article is to study the intake of iodine through iodized salt at household level and urinary iodine concentration (UIC) among school-aged children (6-12 years). Rapid test for iodine content in households salt was carried out throughout the country (280.000 households). Meanwhile, the UIC of 8.250 children’s casual urin sample were carried out from 30 selected districts/cities. Selection of 30 districts/cities was using stratified random sampling from all districts/cities throughout the country. Overall, from the rapid test survey showed that 62,3% households salt contained sufficient iodine. Only 14% of households salt contained no iodine. The median value of UIC among school-aged children was 224 µg/L or far higher than the define population of iodine deficiency. The distribution of UIC values were as follows: 12,9% of children had UIC value less than 100 µg/L, 65,2% between 100-299 µg/L, and 21,9% had UIC value 300 µg/L or over. UIC value of 300 µg/L or over is regarded as having the risk of iodine excess. Children with UIC value 300 µg/L or over were found in almost all of the districts/cities. The majority of household salt contained iodine but has not reached the universal salt iodisation. Median value of UIC of school age children that is the proxy of iodine intake is under the tolerable upper intake level.Keywords: school aged children, household, iodized salt, urinary iodine